Association between glucosamine use and cancer mortality: A large prospective cohort study - Zhou, Jian; Wu, Ziyi; Lin, Zhengjun; Wang, Wanchun; Wan, Rongjun; Liu, Tang (Frontiers in Nutrition, 2022)
Abstract Objective: Previous study on glucosamine indicated anti-cancer and anti-inflammatory benefits. This study was performed to prospectively evaluate the association between glucosamine supplementation and mortality of multiple cancers based on UK Biobank cohort study. Methods: A total of 452,451 participants aged between 38 and 73 who had no cancer at baseline were included between 2006 and 2010 and followed up to March 2021. We used cox proportion hazards model to explore the association between habitual use of glucosamine and cancer mortality. We conducted subgroup analysis to understand the potential effect modifications from demographics, lifestyle factors and health outcomes. Sensitivity analysis was performed to observe the robustness of the results. Results: 88,032 (19.5%) participants reported habitual glucosamine use at baseline. There were 9,363 cancer deaths during a median follow-up of 12.1 years and we observed a significant association between the use of glucosamine and lower overall cancer mortality (HR=0.93, 95% CI=0.87-1.00, p<0.05) and lung cancer mortality (HR=0.84, 95% CI=0.72-0.97, p<0.05). Subgroup analysis showed that habitual glucosamine supplementation was correlated with lower overall cancer mortality among participants who were over 60 years old, male and not obese. We found that the use of glucosamine was connected to lung cancer in participants who were over 60 years old, white, female and not obese. Glucosamine supplementation was related to prostate cancer mortality in participants without high cholesterol and rectum cancer mortality in males. Sensitivity analysis showed that the results we obtained was stable. Conclusion: Habitual glucosamine use was significantly related to a decreased overall cancer and lung cancer mortality, based on data from the large-scale nationwide prospective UK Biobank cohort study.